UPAYA DINAS KOPERASI USAHA MIKRO KECIL DAN MENENGAH KABUPATEN BENGKALIS DALAM MENINGKATKAN KINERJA KOPERASI DI KECAMATAN BENGKALIS TAHUN 2011 - Mohd Abduh Herawza; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The research present describe the Coperation, small micro and middle Bengkalis Agency Regency agency efforts in increase a human resources of coperation in Bengkalis district in 2011. Coperations are economic institution that have purpose to support economic society.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Bengkalis district Bengkalis Regency and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan likes Head Agency of Coperation, micro small and middle Bengkalis Agency, Head of UKM Bengkalis Regency and staff of coperation in Bengkalis district.The conclution of this research are small micro and middle Bengkalis Agency Regency agency efforts has done by optimalization coperations rule with increase of human resources, advice the stafff of coperation Bengkalis district. And some factors influence that cause communication factors, human resources factors, participation of coperation staff was little and understanding of coperation rules.Keywords: effort, agency, rules and coperation.